İlm-i nücûm and its role in the Ottoman court during the eighteenth century - Kırkoğlu, Remzi Hakan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
This thesis examines ilm-i nücûm (astrology) and its practice in the context of Ottoman court dynamics, particularly focusing on the reign of Mustafa III (1757- 1774). With roots in earlier Islamicate cultures, practice of ilm-i nücûm was an imperial tradition of service to the sultan and his close entourage in the Ottoman court. Firstly, the present study explains the transmission of astrological ideas to the Ottoman realm and investigates the reception of ilm-i nücûm by Ottoman scholars. It emphasizes that Ottoman astrological literature explicitly demonstrates that ilm-i nücûm was an integral component in the preoccupations of the ilmiye class. Secondly, this thesis, by investigating the ahkâm works of an eighteenth-century chief-müneccim, Halil Efendi, sheds light on the intertwined relationship between his narratives and prevailing conditions in and around court life. The politically subordinate nature of ahkâm texts provides another look into the vulnerabilities of courtly issues. Meanwhile, we attempted to reconstruct intellectual interests of an eighteenth-century müneccim investigating his estate in the registers. Furthermore, we find that the neatly formatted framework of ahkâms was in fact used in service of the construction of the imperial edifice in cosmological terms. Apart from its routine functions, political astrology, this study argues, has been especially influential during times of major change and uncertainty.
Keywords: Astrology, Turkish -- History.